The Influence of Futsal on the Development of Life Skills of Students at Public Junior High School 1 Parongpong - Dhea Yolanda Azalia; Helmy Firmansyah; Tite Juliantine (Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of futsal learning on the development of students’ life skills at public junior high school 1 Parongpong. The approach used is quantitative with a quasi-experimental method and nonequivalent control group design. The research sample consisted of two groups, namely the experimental group that received futsal learning based on life skills and the control group that followed conventional futsal learning. The research instrument used a validated and reliable life skills questionnaire. The results of data analysis using paired sample t-test and independent sample t-test showed that there was a significant increase in life skills in the experimental group compared to the control group. These findings indicate that futsal learning that integrates life skills values such as cooperation, communication, leadership, and decision making, can provide a positive contribution to students’ personal and social development. Thus, futsal can be utilized strategically as a learning medium that not only emphasizes physical aspects, but also strengthens students’ character and life skills.